The Impact of Carbon Emission Disclosure and Tax Incentives on Firm Value: Evidence from Energy Sector Companies Listed on the Indonesia Stock Exchange (2022-2024) - Ilham Tri Jaya Kusuma; Moh Yudi Mahadianto; Asep Basuki (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
This study examines the effect of carbon emission disclosure and tax incentives on firm value in energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Amid increasing global pressure for sustainable business practices and climate change mitigation, companies are encouraged to enhance environmental transparency and optimize fiscal policies to improve their market performance. This research adopts a quantitative approach with an explanatory design. The sample consists of 39 energy sector companies, resulting in 117 observations selected through purposive sampling. Secondary data were obtained from annual reports, sustainability reports, and financial statements. Carbon emission disclosure was measured using the Carbon Emission Disclosure Checklist, tax incentives were proxied by tax benefits relative to total assets, and firm value was measured using Tobin’s Q. The data were analyzed using multiple linear regression. The results indicate that carbon emission disclosure has a positive and significant effect on firm value, tax incentives also have a positive and significant effect on firm value, and both variables simultaneously influence firm value. These findings suggest that environmental transparency and effective utilization of tax incentives are positively perceived by investors as signals of corporate commitment to sustainability and financial efficiency. This study contributes to the literature on sustainability accounting, taxation, and corporate finance, and provides practical insights for companies, investors, and policymakers in promoting sustainable business practices to enhance firm value.